IoT based smart traffic control system using sumo traffic simulator - Hossain, Sk Md Sunny; Musaab, Mushfiqur Rahman; Taqi, Mohammad Salman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.